Current practice for genetic counselling by nurses: An integrative review. Issue 2 (20th February 2018) - Barr, Jennieffer A.; Tsai, Lily P.; Welch, Anthony; Faradz, Sultana M.H.; Lane‐Krebs, Katrina; Howie, Virginia; Hillman, Wendy
Abstract: Aim: To examine current practice of genetic counselling by nurses. Background: Recent debate argues that genetic counselling is a specialist advanced practice role, whilst others argue it is the role of all nurses. Current evidence is required to determine if genetic counselling could be included in all nurses' scope of practice. Design: Integrative literature review. Data Sources: A search of electronic databases (CINHAL, Medline, PubMed, Scopus), and reference lists published between January 2012 and March 2017, was undertaken. Review Methods: Studies were critically appraised for methodological quality using the Critical Appraisal Skills Programme. Data from each study were extracted and categorized according to their primary findings. Results: The inclusion criteria were met in 10 studies. Main findings were identified: role of genetic counselling, current knowledge, need for further education, and client satisfaction with nurse genetic counsellors. Conclusion: This paper concludes that some nurses do engage in genetic counselling, but how they engage is not consistent, nor is there consensus about what should be the scope of practice. Further investigation into credentialing, role recognition support and education for nurse genetic counselling are strongly recommended. As nurses are widely available, nurses can make a significant contribution to supporting those affected by genetic problems. Abstract : What is already known about this topic? Since the 1970s, nurses have begun to incorporate genetics into their practice, and recent developments in genetic nursing have led to describing roles and responsibilities of genetic nurses. Nurses are well positioned to provide information, assessment, education, and counselling related to genetic health issues; however, the degree to which nurses adopt these roles varies between countries. Research is required to provide a clear understanding of the roles related to genetic counselling nurses are undertaking. What this paper adds? Nurses identified that providing genetic counselling is within their scope of nursing practice. The profession of genetic counsellor is still in high demand, whilst the role of a nurse in genetic counselling is still rare. Clients identified satisfaction with genetic counselling provided by nurses. The implications of this paper: As nurses are widely available, nurses can make a significant contribution to preventing and supporting those affected by genetic problems. Further investigation into credentialing, role recognition, and education for nurse genetic counselling is recommended. Education, support systems, and a clear definition of roles and responsibilities of nurse genetic counsellors are required.